Effects of input filter on stability of matrix converter using venturini modulation algorithm - Erdem, Ebubekir; Tatar, Yetkin; Sünter, Sedat (My University, 2010)
In this paper; simulation, design, and implementation of three-phase to three-phase matrix converter using Venturini modulation algorithm have been presented. Furthermore, effects of input filter on stability of matrix converter have been examined. A Simulink model has been developed in such a way that it supports real time work with the use of DSP control card supported by Simulink. Simulation and experimental results for the input and output waveforms of the matrix converter using R-L load are given at various operating conditions. Good agreement was obtained between the simulation results and the results obtained from the prototype. © 2010 IEEE.
2010 International Symposium on Power Electronics, Electrical Drives, Automation and Motion, SPEEDAM 2010 -- 14 June 2010 through 16 June 2010 -- Pisa -- 81684
Keywords: Matrix converter; Venturini modulation algorithm